2005
DOI: 10.1111/j.1813-6982.2005.00013.x
|View full text |Cite
|
Sign up to set email alerts
|

Economic Growth and the Structure of Taxes in South Africa: 1960-2002*

Abstract: One tenet of taxation is its distorting effect on economic behaviour. Despite the economic inefficiencies resulting from taxation, it is widely believed that taxes impact minimally on the economy's growth rate. Evidence in developing countries generally supports this view. In this paper, we present evidence that tax distortions in South Africa may be much more severe. Using tax and economic data from 1960 to 2002 and a two-stage modelling technique to control for unobservable business cycle variables, we exami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
11
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(16 citation statements)
references
References 18 publications
(16 reference statements)
4
11
0
Order By: Relevance
“…We also find that over the sample period the elasticity of growth to changes in tax structure, that is, tax burden and tax mix has been relatively low except during the ZIMPREST period (1996)(1997)(1998)(1999)(2000). Our findings agree with the current empirical evidence, for example, Koch et al (2005) who find a negative relationship between tax structure and growth in South Africa. We compute the dead weight loss in the economy due to inefficiency and get very alarming results.…”
Section: Resultssupporting
confidence: 79%
See 1 more Smart Citation
“…We also find that over the sample period the elasticity of growth to changes in tax structure, that is, tax burden and tax mix has been relatively low except during the ZIMPREST period (1996)(1997)(1998)(1999)(2000). Our findings agree with the current empirical evidence, for example, Koch et al (2005) who find a negative relationship between tax structure and growth in South Africa. We compute the dead weight loss in the economy due to inefficiency and get very alarming results.…”
Section: Resultssupporting
confidence: 79%
“…Major spikes in growth reflect the vagaries of climate. In 1984In , 1987In , 2002In , 2005In and 2008 there were droughts. The case for the year 2000 coincides with the land reform programme and sanctions imposed on Zimbabwe.…”
Section: Economic Growth and Taxes: A Review Of The Literaturementioning
confidence: 99%
“…These were found to be negatively affected by economic growth. Koch et al (2005) use a methodology similar to the one employed by Lovell and Branson (2001) to present evidence about tax distortions in South Africa. Using data from 1960 to 2002 and a two-stage modeling technique to control for unobservable business cycle variables, they find that decreased tax burdens are strongly associated with increased economic growth; in addition, contrary to most theoretical research, decreased indirect taxation is strongly correlated with increased economic growth potential.…”
Section: Theoretical Reviewmentioning
confidence: 99%
“…Some countries increase taxes while others do not alter their policies regarding taxation. Koch et al (2005) found income tax and economic growth has direct relationship in South Africa. Ebimobowei and Ebiringa (2012) investigated the growth of Nigeria during 1970 to 2010.…”
Section: Introductionmentioning
confidence: 99%